Construction of the self paternity in male teenagers who belong to municipal high schools of La Cisterna commune - Anabalón Armijo, Cecilia; Cares Pozo, Francisca; Cortés Belmar, Ricardo; Zamora Contardo, Macarena (Revista de Psicología, 2011)
This research’s aim is to understand the linkages between the elements of social context, family and school in the construction of one’s parenting, in male adolescents who belong to public high schools in the district of La Cisterna. This qualitative study is focused on phenomenology, hermeneutics perspective, and in-depth interviews as the technique of data collection. The main result was that the most significant area for the construction of fatherhood is family, and as an antagonic area, they identified the figure of the peer group. Also, all the results of this study report the emergence of a new fatherhood.